Prader-Willi Syndrome in Neonates - J Gordon Millichap (Pediatric Neurology Briefs, 1990)
A retrospective study of 16 patients identifying physical features of neonates with Prader-Willi syndrome is reported from the Department of Pediatrics, Division of Genetics, William Beaumont Hospital, Royal Oak, MI and Section of Genetics, Department of Pediatrics, University of Arizona, Tucson.